2019
DOI: 10.1101/688093
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Simultaneous Targeting of XPO1 and BCL2 as an Effective Treatment Strategy for Double-Hit Lymphoma

Abstract: Double-hit lymphoma (DHL) is among the most aggressive and chemoresistant lymphoma subtypes.DHLs carry genomic abnormalities in MYC, BCL2 and/or BCL6 oncogenes. Due to simultaneous overexpression of these driver oncogenes, DHLs are highly resistant to the frontline therapies. Most DHLs overexpress both MYC and BCL2 driver oncogenes concurrently. We reasoned that simultaneous suppression of the two driver oncogenes would be more effective in eradicating DHLs than inactivation of single oncogene. XPO1 is a recep… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Combined use of XPO1 and BCL2 inhibitors is highly synergistic in vitro in eradicating DHL cells. In a mouse model of DHL bearing primary patient-derived xenograft tumor cells, combined treatment with XPO1 and BCL2 inhibitors blocks tumor progression and extends host survival [9]. Of particular interest, we found that the animals treated with the drug combination exhibit significantly lower brain metastasis compared with other groups.…”
mentioning
confidence: 76%
“…Combined use of XPO1 and BCL2 inhibitors is highly synergistic in vitro in eradicating DHL cells. In a mouse model of DHL bearing primary patient-derived xenograft tumor cells, combined treatment with XPO1 and BCL2 inhibitors blocks tumor progression and extends host survival [9]. Of particular interest, we found that the animals treated with the drug combination exhibit significantly lower brain metastasis compared with other groups.…”
mentioning
confidence: 76%
“…Nonetheless, recent experimental studies suggest that XPO1 ‐mutated cells are preferentially sensitive to XPO1 inhibitors 7 . Moreover, the combination of XPO1 and BCL2 inhibitors blocks tumour progression and extends survival in a lymphoma mouse model 15 . These experimental data suggest that combining XPO1 inhibitors with BH3‐mimetic‐based therapy could be of interest in R/R patients with XPO1 mutations.…”
Section: Figurementioning
confidence: 98%